Portable Trolley Box Design As Practice Support At Aviation Polytechnic Surabaya - Siahaan, Binsar; Khalifah Ahmad, Addien; Suyatmo, Suyatmo (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
Every time we visit a shop in the hangar we will find many tools, because tools are tools for cadets and instructors to do maintenance or repairing in the hangar. Trolley is a common tool to make it easier for humans to carry, move, lift something. Trolley is also a dead tool and not machined, then the trolley is run manually by being pushed, it can be seen in all types of trolley that has a handle as a handle to push. And there has not been found a portable trolley box in the hangar to facilitate cadets when carrying out practice or maintenance. To achieve this goal, it is necessary to design and build a portable trolley box that will be used by cadets when carrying out maintenance or repairing in shop or in hangar. This article discusses how to design and build a portable trolley box tool designed by the author himself. By using the help of additional applications such as solidwork, the author can make this design. The results showed that the portable trolley box design has the ability to carry and store tools and components needed for maintenance with a larger size and also more. The conclusion from the research results of this portable trolley box design is that it can facilitate cadets in maintenance or aircraft maintenance.